Answer:
1) y = 5, x = 2
2) y = 5, x = 8
3) y = -2, x= -2
Explanation:
1)
Use elimination to solve this problem. In this case, one can just add up the two equations, simplify, use inverse operations, and then substitute back in to find the answer.
y = -x + 7
y = x + 3
_______
2y = 10
/2 /2
y = 5, x = 2
2)
Use elimination, in this case, one will have to multiply the second equation by -2, then add, in order to eliminate one of the variables. Finally one will have to simplify, use inverse operations and then substitute back in to solve.
y = x - 3
y = (1/2)x + 1 (*-2)
y = x - 3
-2y = -x - 2
-y = -5
y = 5, x = 8
3)
Use elimination, in this case, one will have to multiply the second equation by 2, then add, in order to eliminate a variable. Then one will have to simplify, use inverse operations and then substitute back in to solve.
y = 2x + 2
y = -x - 4 *(2)
y = 2x + 2
2y = -2x - 8
3y = -6
/3 /3
y = -2, x = -2